Evaluation of the different biomaterials used in alveolar cleft defects in children - Ferreira, Pedro Henrique Silva Gomes [UNESP]; De Oliveira, Danila [UNESP]; De Deus, Ciro Borges Duailibe [UNESP]; Okamoto, Roberta [UNESP] (Wolters Kluwer, 2018)
The aim of this study was to use a literature review to evaluate and compare the different biomaterials used in surgeries for the closure of the palatal and alveolar clefts as alternatives to isolated autografting. For the search strategy, the PubMed and Medline databases were used with the indexing terms ''cleft palate' (Mesh), 'biocompatible materials' (Mesh), and 'dentistry' (Mesh).' There was no restriction on language or publication time. After the research, 26 articles were found, and then, only the filter for clinical trials was selected. With this methodology, five articles were selected. The full texts have been carefully evaluated. The main issue among the five selected articles was the closure of a cleft palate and/or alveolar bone with the use of different types of biomaterials (e.g. autogenous bone from the iliac crest and chin, deproteinized bovine bone (DBB), β-Tricalcium phosphate (β-TCP), synthetic resorption based on calcium sulfate, and the engineering of bone tissue); they evaluated preoperative and postoperative clinically and through imaging tests. The autogenous bone associated with DBB or β-TCP significantly reduces the amount of autogenous bone harvested from the iliac crest, morbidity, and the hospitalization of the patient, and the isolated use of bovine hydroxyapatite resulted in lower bone density compared to that from autogenous bone.
Keywords: Alveolar bone grafting; biocompatible materials; bone transplantation; cleft palate